Impact of ethnicity and neighborhood deprivation on preterm birth: How does urban living play a role?. (March 2023) - van Winden, Tijn; Roos, Carolien; Hanna, Ameen Abu; Pajkrt, Eva; Oudijk, Martijn A.; Ravelli, Anita C.J.
Abstract: Objective: Women of Black and other non-Western ethnicity and women who live in deprived neighborhoods are at increased risk for preterm birth (PTB). These women may live clustered in certain urban areas. If ethnicity reflects a biological rather than a socioeconomic risk factor, women should have a PTB risk independent of the urban area where they live. In this study we explored the association between urban living and the risk of PTB, combined with knowledge on ethnicity and neighborhood deprivation in these specific urban areas in the Netherlands. Study design: National cohort study of 935, 381 women (2014–2019) with a singleton pregnancy resulting in live birth between 24.0 and 42.6 weeks. Antepartum death and severe congenital anomalies were excluded. We performed logistic regression analysis and analyzed the impact of living in one of the four main urban areas on PTB. We adjusted for maternal age, parity and fetal gender. We tested for interaction between ethnicity, neighborhood deprivation index (NDI) and urban living. Results: Mean PTB rate among singleton pregnancies in The Netherlands is 5.1%. There was a strong ethnic difference in PTB risk, with the highest prevalence among South Asian women (7.9%) and African women (6.6%). In the most deprived neighborhoods the PTB risk was 5.7%. We found a significant interaction between ethnicity and urban living, and between NDI and urban living. South Asian and African women living in urban areas had the greatest risk of PTB, between 7.0% and 8.8%. Conclusion: Ethnicity remains a fixed biological risk for PTB that cannot be fully explained by socioeconomic status or neighborhood deprivation. Independent of ethnicity and neighborhood deprivation, urban living has a great influence on the risk of preterm birth. Future studies and policies should focus on population-based interventions in those urban areas where South Asian and African ethnic groups live and where the preterm birth risk is the highest.